OP89 Quantifying bias due to regression to the mean in lifecourse analysis. (13th September 2016) - Gadd, SC; Arnold, K; Ellison, GTH; Textor, J; Gilthorpe, MS
Abstract : Background: Within lifecourse epidemiology, there is substantial interest in relationships between exposures (X) that are measured longitudinally (e.g. at time 0, 1, 2; hence X0, X1, X2 ) and outcomes (Y) that are measured once, cross-sectionally (e.g. Y2 or Y2+t ). Methods used to analyse these relationships often involve conditioning on the outcome and suffer regression to the mean (RTM), making causal inference challenging. The aim of our study was to demonstrate this and to quantify the potential bias that can ensue across a range of different scenarios. Methods: Directed acyclic graphs (DAGs) were used to depict a range of potential causal relationships between an exposure measured longitudinally (BMI: body mass index; e.g. at ages 2, 15 and 64 years; BMI2, BMI15 and BMI64 ), and a later-life outcome (CRP: C-reactive protein, a marker for cardiovascular disease) measured once around the time of the last exposure measurement (CRP> 64 ). The covariance structure and mean values of each variable were obtained from the literature to inform simulations for three scenarios where: (i) CRP> 64 is not caused by BMI2, BMI15 or BMI64 ; (ii) CRP> 64 is caused only by BMI64 ; and (iii) CRP> 64 is caused by more than one of BMI2, BMI15 and/or BMI64 . Results: In scenario (i), BMI2, BMI15 and BMI64 are not causally related to CRP> 64, yet 'trajectories' will be seen when plotting BMI conditioned on the outcome, generating spurious causal interpretation. If CRP> 64 is caused by BMI64 only, as in scenario (ii), the estimated direct impact of BMI2 and/or BMI15 on CRP> 64 is spurious. If CRP> 64 is directly caused by more than one BMI exposure, as in scenario (iii), the estimated causal impact of BMI at any given time point on CRP> 64 can be biassed, the extent of which depends on the specific correlation structure amongst all measures of BMI and CRP> 64 . These results arise due to RTM caused by conditioning BMI 'trajectories' on CRP> 64 and indicate considerable scope for misinterpretation of the direct causal impact of one or other measure of BMI on CRP> 64 . Conclusion: With no causal relationship between changes in an exposure measured longitudinally, and a later-life outcome, spurious relationships will emerge if any of the individual measures of exposure are correlated with the outcome. With a genuine causal relationship between any measure of a longitudinal exposure and later-life outcome, the estimated relationship of the exposure at any one time point may be biassed, leading to erroneous causal interpretations.